3D navigation based on 3D game engine – preliminary results - Sharkawi, Khairul Hafiz (Penerbit UTM, 2008)
With new technology of hardware a nd software available today, more and more research on 3D capabilities were carried out, tested and incorporated with GIS as an effort to realize the components of 3D GIS such as 3D navigation. Many navigation systems use 2D maps to represent the real world objects and situations; and most of them were not able to provide real spatial information (shapes, colors or materials) of the objects or scenes, as we perceiv ed. Features and navigational landmarks were not easil y available for navigating in the real world, as they were very useful and helpful for the navigation purposes. This chapter describes an experiment on 3D navigation (indoor and outdoor) with in building environm ent. We utilize a freely available 3D game engine as a navigation tool couple with simple programming effort. We also incorporated the navigation system with spatial database management system (DBMS). The navigation system works and will be presented. The outlook and future works on the proposed navigation system for 3D GIS will be highlighted.